2018
DOI: 10.1016/j.jcs.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of yeast metabolites on the rheological behaviour of the dough matrix in fermented wheat flour dough

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 19 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…Whereas the concentration of the other main yeast metabolites (ethanol, succinic acid, glycerol) was found to in-crease gradually over time (Jayaram et al, 2013), small amounts of glutathione may indeed be present in dough already at the beginning of fermentation, and may bring about a substantial softening of the dough matrix (Verheyen et al, 2015). However, no experimental evidence could be found that glutathione specifically targets the dough response at low frequencies (Meerts et al, 2018).…”
Section: The Time-dependent Rheology Of Fermenting Doughmentioning
confidence: 97%
See 3 more Smart Citations
“…Whereas the concentration of the other main yeast metabolites (ethanol, succinic acid, glycerol) was found to in-crease gradually over time (Jayaram et al, 2013), small amounts of glutathione may indeed be present in dough already at the beginning of fermentation, and may bring about a substantial softening of the dough matrix (Verheyen et al, 2015). However, no experimental evidence could be found that glutathione specifically targets the dough response at low frequencies (Meerts et al, 2018).…”
Section: The Time-dependent Rheology Of Fermenting Doughmentioning
confidence: 97%
“…A distinction has to be made, therefore, between on the one hand the effect of the CO 2 gas bubbles and on the other hand the impact of changes in the viscoelastic dough matrix due to fermentation. All in all, the impact of fermentation on the rheology of the dough matrix was found to be rather limited in degassed fermented dough (Meerts et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…During the fermentation step, CO 2 and many secondary metabolites are generated by yeast cells and released into the dough matrix phase due to common metabolic activity, or, in case of osmotic stress, to maintain the internal redox balance [ 7 ]. An often-underestimated effect is the impact of secondary metabolites on the rheological properties of the dough matrix, clearly determining the manufacturing properties and end product characteristics [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Thus, the aim of the current study is to characterise the rheological behaviour of the fermenting dough matrix for relevant deformation types and strain rates occurring during the breadmaking process.…”
Section: Introductionmentioning
confidence: 99%